Continuous and pulse‐feeding application of multispecies probiotic bacteria in whiteleg shrimp, Litopenaeus vannamei. Issue 6 (1st August 2019) - Kesselring, Jutta C.; Gruber, Christina; Standen, Benedict; Wein, Silvia
Abstract: Probiotic bacteria are known to support the gut health of shrimp and thereby improve performance and production efficiency. Among other factors, the timing of probiotic application is of importance. Thus, this experiment (12‐week feeding trial followed by intramuscular Vibrio challenge) aimed to compare the effects of a multispecies probiotic feed supplement (AquaStar® Growout, 3 g/kg feed) in a continuous application with three different alternating application protocols on growth performance and immune parameters in whiteleg shrimp, Litopenaeus vannamei . Juvenile shrimp were stocked in a recirculating aquaculture system at a density of 15 shrimp/100 L and were fed an appropriate commercial diet throughout the whole trial. Tanks were randomly assigned to the treatments, and shrimp were fed one of the following five experimental treatments: T1: no probiotics (control), T2: probiotics continuously, T3: alternating 1 week probiotics, 1 week control, T4: alternating 2 weeks probiotics, 2 weeks control, or T5: alternating 2 weeks probiotics, 1 week control. While any AquaStar® Growout application significantly improved growth performance, only continuous application delayed mortality after the Vibrio challenge. Results suggest that the beneficial effects were most pronounced when AquaStar® Growout was fed either continuously or according to the T5 treatment.